FACTORS INFLUENCING THE SUCCESSFUL IMPLEMENTATION OF SAP - Yusoff, Siti Khalidah Mohd; Azam, S.M. Ferdous; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
SAP was founded in 1972 in Walldorf, Germany. It stands for Systems, Applications and Products in Data Processing. The main advantage of using SAP as your company ERP system is that SAP has a very high level of integration among its individual applications which guarantee consistency of data throughout the system and the company itself. This paper gives brief guidelines what organization should consider when they planned to implement SAP ERP in their business. The study focused to analyze the factors that effect on the implementation of SAP. For analyzing the factors that place effects, some variables like, project preparation, technology selection has been elected in this study. While on the basis of such variables data has also been collected to analyze the influence. Regression and correlation analysis has been performed in this study, where the results were significant in context of relationships and influence between them.Keywords---, , , , , .